Prevalence of resistance-associated mutations in Human Immunodeficiency Virus type 1-positive individuals failing HAART in Rio de Janeiro, Brazil - Varella,Rafael Brandão (2008)
We investigated the occurrence of HIV-1 antiretroviral resistance in individuals failing to respond to highly active antiretroviral therapy (HAART) attended by RENAGENO from 2001-2004. One hundred and seventeen patients were selected for this study; their plasma viral RNA was extracted and the PR and RT genes sequenced to examine subtype, genetic polymorphisms and mutations associated with resistance to antiretroviral drugs. HIV-1 sequence analysis showed that 86/100 (86%) were infected with subtype B, 7/100 (7%) with subtype F and 7/100 (7%) with RT/PR hybrid forms (2 D/B, 2 F/B, 2 B/F and 1 D/F). In 14 (12%) of the samples, the subtype was not determined. The prevalence of resistance mutations was high (93.1%), mainly in the RT gene. The most prevalent resistance mutations were: M184V (60.7%), T215Y (49.6%) and M41L (46.7%) in the RT gene and L90M (19.6%), M46I (16.2%) and D30N (12.8%) in the PR gene. The frequency of resistance mutations tended to increase from the first to the second therapeutic scheme failure (p=0.079); but it stabilized after subsequent failures (p=0.875). Our finding of a high frequency of drug resistant HIV-1 samples supports the need for continuous genotypic monitoring of patients failing HAART.